International social security law: the history of the formation and role of the International Labour Organization - Postovalova, Tatjana (Journal of the Belarusian State University. Law, 2019)
The problem of correlation and interaction of international and national law is one of the pressing and complex issues of jurisprudence. The right of social security was expressed in the Universal Declaration of Human Rights. The role of such social security standards-setting Organization as by the International Labour Organization was analyzed. Special attention is paid to the analysis of the International Labor Organization Convention No. 102 on Minimum Standards of Social Security (1952). This article critically examines the approach of the International Labour Organization of supervision of the ILO Standards. The International Labour Organization develops the system of conventions on social security. The ILO Conventions has only minimal standards on social security. The author analyzes the problems of the lack of interest of states in ratifying the ILO conventions on social security. It articulates several difficulties in adoption of the ILO Standards in the majority of developing countries.